Pola Komunikasi Pemuda Karang Taruna Desa Kejapanan Penggemar Game Online Mobile Legend - Wibisono, Gunawan Rico; Asy'ari, Nur Aini Shofiya (Program Studi Ilmu Komunikasi, 2025)
The phenomenon of digitalization has transformed the communication patterns of the younger generation, including through virtual features in online games such as Mobile Legends. This is also evident among members of the Karang Taruna youth organization in Kejapanan Village, who actively interact through the game despite being physically apart. This study aims to analyze their communication patterns using the theory of Tubbs and Moss, which includes linear, interactional, and transactional communication models. The research employs a qualitative descriptive method with data collection techniques including interviews, observation, and documentation. The research subjects consist of five Karang Taruna members who actively play Mobile Legends, selected based on their involvement in the organization and consistent participation in the game. Data analysis was conducted using the Miles and Huberman model to gain an in-depth understanding. The findings reveal that linear communication patterns occur in situations requiring quick decision-making, such as when securing major objectives in the game. Interactional communication patterns emerge during the initial strategy planning stages, where team members exchange information and respond to one another. Meanwhile, transactional communication patterns are more dominant in dynamic gameplay situations, where communication occurs simultaneously and flexibly among team members. The study also found that in-game interactions contribute to strengthening social relationships among Karang Taruna members, enhancing solidarity, and facilitating coordination in community activities. Thus, this research provides new insights into the dynamics of communication within youth-based digital communities and their implications for real-world social interactions.